STUDY ON THE USE OF SIDEWALKS IN THE CITY OF PURWOKERTO, BANYUMAS DISTRICT - Corona Dwi Istiningsih; F. Eddy Poerwodihardjo (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2019)
Walking is an activity that is always carried out by everyone. Walking activity requires an area orcontainer. The sidewalk is an area reserved specifically for pedestrians in movement, and is a safe place forpedestrians to move. Everyone, from children, adults, parents and even elderly people need sidewalks as ameans of movement. People with disabilities and The sidewalk is always next to the road. The situation made the sidewalk a strategic place, and easilyaccessible, so that it attracted many people to take part in making use of it. The use of sidewalks is no longerfor pedestrians only. There are several uses that are not in accordance with the function of the sidewalk.These uses include; sidewalks are used for trading by street vendors. Sidewalks are used for businessexpansion. The sidewalk is used as a parking area for both 2-wheeled and 4-wheeled four-wheeled vehicles.Utilization is then given the name of the sidewalk utilization function. There are 2 (two) uses of the sidewalk, the author will reveal the two uses that have occurred on thesidewalk. The fact that this happens is that the sidewalks have been well utilized by pedestrians. All people ofall ages can make good use of it. The disabled are still lacking, and the most populous utilization time ismorning and afternoon. There are 66% of sidewalks on which there are functions of sidewalk utilization.Observations show that both uses occur in a single sidewalk, and the results show that on sidewalks withhigh conversion there is a low utilization. Keywords: sidewalk, pedestrians, sidewalk utilizationABSTRAK Berjalan adalah aktivitas yang selalu dilakukan oleh setiap orang . Aktivitas berjalan membutuhkan suatu area atau wadah. Trotoar adalah area yang disediakan khusus untuk pejalan kaki dalam pergerakan,dan menjadi tempat yang aman bagi pejalan kaki dalam beraktivitas. Semua orang , dari anak-anak, orangdewasa, orang tua bahkan orang lanjut usia membutuhkan trotoar sebagai sarana dalam pergerakannya.Kaum difabel dan Letak trotoar selalu bersebelahan dengan jalan. Keadaan tersebut menjadikan trotoar tempat yangstrategis, dan mudah dicapai, sehingga menarik banyak orang untuk turut memenafaatkan. Pemanfaatantrotoar tidak lagi untuk pejalan kaki saja. Terdapat beberapa pemanfaatan yang tidak sesuai dengan fungsidari trotoar. Pemanfaatan tersebut antara lain; trotoar digunakan untuk berdagang oleh Pedagang Kaki Lima (PKL ). Trotoar digunakan untuk perluasan tempat usaha. Trotoar digunakan sebagai area parkir kendaraanbaik roda 2 (dua) maupun roda 4 (empat). Pemanfaatan tersebut, selanjutnya diberi nama alihfungsipemanfaatan trotoar. Terdapat 2 ( dua) pemanafaatan trotoar , penulis akan mengungkap kedua pemanfaatan yang telah terjadi di trotoar. Kenyataan yang terjadi adalah trotoar sudah dimanfaatakan dengan baik oleh pejalan kaki.Semua orang dari berbagai umur telah dapat memanfaatkan dengan baik. Kaum difabel masih sangat kurang,dan waktu pemanfaatan terpadat adalah pagi dan siang hari. Terdapat 66 % trotoar yang di atasnya terdapatalihfungsi pemanfaatan trotoar. Hasil pengamatan menunjukkan bahwa kedua pemanfaatan terjadi dalam satutrotoar, dan diperoleh hasil bahwa pada trotoar dengan alihfungsi tinggi terdapat pemanfaatan yang rendah.Kata kunci : trotoar,pejalan kaki, pemanfaatan trotoar)